New states and international law - Anand, R.P. (Gurgaon, 2008)
This is a valuable addition to the already existing mass of literature on the subject. The author points out that every norm of International Law, it it is really to be International, must serve the need of all states, small and large, new and old, weak and powerful.
Keywords: International Law